The Influence Of Socio-Scientific Issues On Reflective Judgment Of High School’s Student In Ecosystem Material - Naafi Aisya; Yuni Wibowo; Tien Aminatun (Universitas Ahmad Dahlan, 2016)
This research is aimed to (1) determined the effect of learning strategy Socio-scientific Issues on students reflective judgment. This research was a quasi-experimental design with pre-test experimental post-test control group. The variables of this study consists of independent variable implementation strategy Socio-scientific Issues, the dependent variable was reflective judgment students ability. The sampling technique used purposive random sampling. The validity of the research instrument used content validity, construct and empirically validity. Test reliability was calculated used Cronbach's Alpha R11= 0.706. Analysis of the data in this study used the Wilcoxon test for reflective judgment. This result showed a significant difference of concept understanding Â and reflective judgment between experimental class and control class with a significance level of 0.000. Thus, it can be concluded that the application of learning strategies Socio-scientific Issues effected on the reflective judgment student on the ecosystem (hydrological cycle) material.